Saving in the world. (April 2018) - Grigoli, Francesco; Herman, Alexander; Schmidt-Hebbel, Klaus
Highlights: We construct the largest dataset available covering 165 countries over 1981–2012 for key saving aggregates. We survey consumption theories to identify saving determinants and review the empirical literature using panel data. Private saving is positively associated with income levels, current and future growth, and inflation. Public saving (with partial Ricardian offsetting), credit, dependency ratios, and urbanization reduce private saving. These results generally hold for other saving aggregates but they differ somewhat across time periods and country groups. Abstract: This paper presents new evidence on the behavior of saving in the world, by extending previous empirical research in several dimensions. After extensively surveying the relevant theoretical and empirical literature, the paper reports estimates of saving determinants relying on the newly constructed and largest available database covering 165 countries over 1981–2012. The empirical specification includes determinants not considered in the literature, explores differences in saving behavior nesting the 2008–10 crisis period and four different country groups, searches for commonalities across key saving aggregates (national, private, household, and corporate saving rates), and is subject to a robustness analysis based on different estimation techniques. The results confirm in part existing research, but also shed light on some ambiguous or contradictory findings and highlight the role of neglected determinants. Compared to the literature, we find a larger number of significant determinants, changes across periods and country groups, and similarities across different saving aggregates.